Highly sensitive, selective and label-free protein detection in physiological solutions using carbon nanotube transistors with nanobody receptors - Filipiak, Marcin Szymon; Rother, Marcel; Andoy, Nesha M.; Knudsen, Arne; Grimm, Stefan; Bachran, Christopher; Swee, Lee Kim; Zaumseil, Jana; Tarasov, Alexey (Sensors and actuators. B, Chemical, 2018)
Nanomaterial-based field-effect transistors (FETs) have been proposed for real-time, label-free detection of various biological species. However, two major challenges have limited their use in physiological samples: screening of the analyte charge by electrolyte ions (Debye screening) and non-specific adsorption. Here, these challenges are overcome by combining highly stable FETs based on single-walled semiconducting carbon nanotube (SWCNTs) networks with a novel surface functionalization comprising: 1) short nanobody (VHH) receptors, and 2) a polyethylene glycol (PEG) layer. Nanobodies are stable, easy-to-produce biological receptors that are very small (∼2-4nm), thus enabling analyte binding closer to the sensor surface. Despite their unique properties, nanobodies have not been used yet as receptors in FET based biosensors. The addition of PEG strongly enhances the signal in high ionic strength environment. Using green fluorescent protein (GFP) as a model antigen, high selectivity and sub-picomolar detection limit with a dynamic range exceeding 5 orders of magnitude is demonstrated in physiological solutions. In addition, long-term stability measurements reveal a low drift of SWCNTs of 0.05mV/h. The presented immunoassay is fast, label-free, does not require any sample pretreatment or washing steps.
Available online 24 August 2017
Gesehen am 17.04.2020